2013
DOI: 10.1002/jtr.1966
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation Adoption among Rural Tourism Enterprises: The Effect of the Location and Characteristics of the Firm

Abstract: This paper highlighted the importance of market orientation as a strategy for the success of rural tourism enterprises. The purpose of the work was to identify an explanatory model for the market orientation adopted by rural tourism enterprises. The explanatory factors identified were as follows: category; information and communications technology use; and the entrepreneur's gender. It was also found that the location of the enterprise relative to its competitors may also influence market orientation adoption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Rural tourism and entrepreneurship Rural tourism is characterised by small family firms (Getz & Carlsen, 2000, 2005Horobin & Long, 1996;Peters & Buhalis, 2013), which are often embedded in specific regional settings that require individual entrepreneurial behaviour to perform well (Morrison, 2006;Polo-Peña, Chica-Olmo, Frías-Jamilena, & Rodríguez-Molina, 2015). Rural tourism was traditionally developed using existing properties (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rural tourism and entrepreneurship Rural tourism is characterised by small family firms (Getz & Carlsen, 2000, 2005Horobin & Long, 1996;Peters & Buhalis, 2013), which are often embedded in specific regional settings that require individual entrepreneurial behaviour to perform well (Morrison, 2006;Polo-Peña, Chica-Olmo, Frías-Jamilena, & Rodríguez-Molina, 2015). Rural tourism was traditionally developed using existing properties (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some studies carried out in the specific sector of tourism confirm how improvements in production are also likely to occur in this sector. This is the case of the work carried out by Polo Pena et al (2015), in which it is confirmed that space agglomeration favors the spread of the adoption of a more market-oriented strategy among rural tourism companies that are spatially grouped.…”
Section: The Importance Of Space In Accommodation Distributionmentioning
confidence: 60%
“…In particular, Barbieri and Mahoney () affirm that farmer entrepreneurs who have diversified into tourism alone (on‐farm and farm‐diverse) are more motivated by a desire to create something or by a so‐called creative urge than they are by a need for additional income. On the other hand, barriers to the successful diversification of farms into tourism activities are diverse (Polo‐Peña, Olmo, Frías‐Jamilena, & Rodríguez‐Molina, ; Sharpley & Vass, ; Su, ; Vik & McElwee, ). First, farm tourism enterprises are small, with returns on significant investments being influenced by a highly seasonal market and by the “neighbourhood effects” of clusters of rural tourism enterprises.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Second, being a tourism entrepreneur requires risk taking and strategic thinking. Third, rural enterprises present characteristics differentiating them from other businesses, such as the central role of the entrepreneur, limited resources to develop management and marketing activities, and an isolated rural location (Polo‐Peña et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%